Transcatheter Edge-to-Edge Repair for Severe Mitral Regurgitation With Double-Orifice Mitral Valve - Xiaoguang Ye, MD; Fujian Duan, MD; Li Xu, MD (JACC: Case Reports, 2024)
Double-orifice mitral valve (DOMV), a rare congenital heart disease, is the inspiration behind the transcatheter edge-to-edge repair (TEER). Here we report a successful TEER case in a patient with DOMV with severe regurgitation. The patient’s symptoms were greatly improved after the procedure.